The Behaviour and Preferences of Foreign Tourists using the Services of Guides in Poznań in 2011-2013 - Rohrscheidt, Armin Mikos von (Studia Oeconomica Posnaniensia, 2014)
This paper discusses the behaviour and preferences of tourists using the services of city guides in Poznań. After outlining the basic needs of a city tourist (on the basis of the existing literature), the author presents the findings of a survey relating to the scope of this research, broken down into the main groups of foreign tourists visiting Poznań according to the language they speak: German, English, Russian and Ukrainian, plus Spanish. Based on the results of this analysis, the subsequent part of the paper presents data relating to these groups of tourists, such as the periods having the highest demand for the services of guides, the main sources of requests for these services, the duration of the services, the most common sightseeing routes, and the most frequently visited places and monuments. Finally, comparing the findings with the results of his previous studies, the author formulates conclusions with regard to improving the structure and quality of the urban tourism product offered to organised groups of tourists.